Draft Genome Sequence of Phomopsis longicolla Type Strain TWH P74, a Fungus Causing Phomopsis Seed Decay in Soybean - Li, Shuxian (Genome Announc, 2015)
Phomopsis longicolla is the primary cause of Phomopsis seed decay in soybean. Here, we report the de novo assembled draft genome sequence of the P. longicolla type strain TWH P74 (ATCC 60325), which was originally isolated by Hobbs et al. from soybean seed in Ohio in 1983.